An introduction to microcomputer systems : - Fulcher, John (Addison-Wesley, 1989)
The book provides a thoroughly modern and up-to-date introduction to microcomputer interfacing, as well as a general introduction to the fundamentals of microcomputer architecture. Discussion of the hardware and software aspects of interfacing are woven together and exemplified by reference to two industry standard 16-bit microprocessors, the Intel i8086 and Motorola 68000. The book contains over 350 diagrams and figures; numerous programming examples based on two standard microprocessors; the objectives and summaries provided for each chapter; questions at the end of all chapters for self-assessment; a list of references for further reading; detailed appendices on the Motorola 68000 and Intel iAPX86 families